Enhancing African Research Visibility Through Use of Repositories - Obanda, Johanssen; Havemann, Jo (My University, 2021)
A presentation about how to Enhance African Research Visibility Through Use of Repositories; held at the TCC Africa webinar on Feb 3, 2021
Keywords: African Research; Repositories; AfricArXiv